Determinants of Customers' Decisions in Choosing Musyarakah Mutanaqisah Financing: The Roles of Personal Selling, Perceived Value, and Perceived Sacrifice - Santi Arafah; Amanda Egi Pratiwi; Khadijah Syaparillah Simamora; Aldi Armadana (Institut Agama Islam Negeri Lhokseumawe, 2026)
This study aims to analyze the determinants of customers decisions in choosing Musyarakah Mutanaqisah (MMQ) financing by examining the roles of personal selling, perceived value, and perceived sacrifice. A descriptive quantitative research design with a cross-sectional approach was employed. The population consisted of 53 customers of PT Bank Sumut Syariah KCPsy Kota Baru Marelan who had used MMQ financing, and all respondents were selected using purposive sampling. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results of the research conducted with a confidence level of 95% based on sig. 5%, states that personal selling, perceived value and perceived sacrifice affect musyarakah mutanaqisyah financing decisions. These findings suggest that strengthening the personal selling of account officers, enhancing customers perceived value, and effectively managing customers perceived sacrifice can improve customers' willingness to choose MMQ financing products in sharia banking.